2009
DOI: 10.1002/bjs.6588
|View full text |Cite
|
Sign up to set email alerts
|

Fasting-induced intestinal damage is mediated by oxidative and inflammatory responses

Abstract: Green tea reverses the fasting-induced damage to the intestinal mucosa by its antioxidant and anti-inflammatory effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Furthermore, Kruidenier et al reported that CuZnSOD staining is observed in the human intestinal epithelium [15], and Abdeen et al reported that SOD expression is high in the intestinal mucosa of the rat jejunum [1]. These results of reports are in agreement with the results of the present study on cecal histology and immunohistochemistry of CuZnSOD in GF and CV mice.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Kruidenier et al reported that CuZnSOD staining is observed in the human intestinal epithelium [15], and Abdeen et al reported that SOD expression is high in the intestinal mucosa of the rat jejunum [1]. These results of reports are in agreement with the results of the present study on cecal histology and immunohistochemistry of CuZnSOD in GF and CV mice.…”
Section: Discussionsupporting
confidence: 92%
“…Recent evidence shows that IEL-derived IFN-␥ evokes enterocyte apoptosis via an upregulation of Fas/FasL, leading to the increase in sensitivity of epithelial cells to Fas-mediated apoptosis (30,56) through the type 1 pathway (56). It has been suggested that complex reciprocal interactions exist between IEC and IEL (20,56); therefore, it is likely that IEC and IEL form a reciprocal feedback loop in which iNOS-released NO, physiologically present in IEC, stimulates IFN-␥ production in IEL through a ROS-mediated mechanism (1,5,38), then IFN-␥ stimulates further iNOS-derived NO production, resulting in further IFN-␥ production and subsequent IEC apoptosis (Fig. 13).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the interaction between intestinal microflora and antioxidant enzyme activity, although there have been some reports on leukocyte function with respect to either O 2 ·-release [18,20], gastrointestinal nitric oxide (NO) generation measurements [27], or expression of GPx, which is a different antioxidant enzyme, found in the cecal mucosa of GF animals as well as CV animals [15]. In the gastrointestinal tract, SOD activity has been reported to determine the therapeutic value of SOD in an experimental model [1,26], but the effect of intestinal microflora on antioxidant enzyme activity is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%